Incidence of BKV in the urine and blood samples of pediatric patients undergoing HSCT. (2nd November 2020) - Yazısız, Hatice; Uygun, Vedat; Çolak, Dilek; Mutlu, Derya; Hazar, Volkan; Öğünç, Dilara; Öngüt, Gözde; Küpesiz, Funda Tayfun
Abstract: The aims were to investigate the incidence of BKV infection and the presence of HC in pediatric patients undergoing HSCT. Twenty‐four children patients (M/F: 17/7) undergoing HSCT in a single center over a period of 1 year were included in the study. The presence of BKV DNA was determined by quantitative real‐time PCR in plasma and urine samples at the following times: before transplantation, twice a week until engraftment time, and weekly for + 100 days. The mean age of the patients was 7.79 ± 5.03 years, the mean follow‐up time was 95.6 ± 25.9 days, and the average number of samples per patient was 15.8 ± 3.2. BKV DNA was detected in at least one urine sample in 91.6% (n: 22) and at least one plasma sample in 75% (n:18) of the patients. The median time to the first BKV DNA positivity in urine and plasma samples was 11 (range: 1‐80) and 32 days (range: 2‐79), respectively. The median value of BKV DNA copies in urine and plasma were 1.7 × 10 6 (range: 2.8 × 10 1 ‐1.2 × 10 14 ) and 1.9 × 10 3 copies/mL (range: 3‐2.1 × 10 6 ), respectively. Thirteen patients (54.2%) had hematuria with BKV viruria; 8 (33.3%) patients had viremia. The median value of the BKV DNA copies in urine and plasma was 4.4 × 10 7 (range: 65‐1 × 10 11 ) and 2.9 × 10 3 (range: 7‐7.8 × 10 4 ) copies/mL in these patients. Two (15.4%) of the 13 patients with BKV viruria and hematuria were diagnosed with BKV‐related HC. BKV DNA viral load monitoring of urine and plasma in pediatric HSCT patients with a high risk for viral infections is valuable for understanding the development of BKV–related HC.